Peningkatan Keterampilan dan Perekonomian Masyarakat Desa Mekar Baru Melalui Pelatihan Pengolahan Ikan Nila - Warsidah Warsidah; Shifa Helena; Syarif Irwan Nurdiansyah (Indonesian Journal Publisher, 2024)
The people of Mekar Baru Village, who live along the banks of the Kapuas River, generally earn their living as farmers cultivating tilapia, goldfish and snakehead fish and tilapia. With the community's low level of education, this has an impact on their lack of understanding about the benefits of consuming fish and their lack of skills in processing fish which can increase the economic value or selling price of the cultivated fish commodity. This community service activity (PKM) aims to improve skills in processing floss and nuggets made from valuable fish meat, so that it can help the family's economy. The activity was attended by 20 activity participants consisting of housewives. This activity was divided into 2 activities, namely a scientific lecture about the benefits of fish and its various derivative preparations in improving family health and direct practice in making tilapia fish shreds and nuggets. The results of the evaluation of this PKM activity show an increase in participants' understanding regarding the benefits of consuming fish or its processed products, as well as improving skills in making shredded tilapia fish floss and nuggets.